2012
DOI: 10.1093/cvr/cvs282
|View full text |Cite
|
Sign up to set email alerts
|

Prior starvation mitigates acute doxorubicin cardiotoxicity through restoration of autophagy in affected cardiomyocytes

Abstract: Prior starvation mitigates acute doxorubicin cardiotoxicity; the underlying mechanism may be, at least in part, restoration and further augmentation of myocardial autophagy, which is impaired by doxorubicin, probably through inactivation of AMP-activated protein kinase and ULK1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
131
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 43 publications
9
131
0
Order By: Relevance
“…15 To confirm whether the observed increase in LC3 dots was due to increased autophagosome formation or impairment of their degradation, we measured in vivo autophagic flux in db/db hearts. 16,17 Under a short-term (4 h) intervention with chloroquine, greater numbers of LC3 dots were immunohistochemically evident in db/C than db/db hearts, and western blot analysis confirmed increased expression of LC3-II in db/C hearts, but not in db/db hearts (Fig. 9).…”
Section: Functional and Structural Profiles Of Hearts From Diabetic Micementioning
confidence: 95%
“…15 To confirm whether the observed increase in LC3 dots was due to increased autophagosome formation or impairment of their degradation, we measured in vivo autophagic flux in db/db hearts. 16,17 Under a short-term (4 h) intervention with chloroquine, greater numbers of LC3 dots were immunohistochemically evident in db/C than db/db hearts, and western blot analysis confirmed increased expression of LC3-II in db/C hearts, but not in db/db hearts (Fig. 9).…”
Section: Functional and Structural Profiles Of Hearts From Diabetic Micementioning
confidence: 95%
“…Indeed, Raffaghello et al [28] reported that 48-60 h of complete fasting prevented organ toxicity induced by chemotherapy in various species of female mice, however, etoposide rather than Dox was used in the study. Kawaguchi et al [29] demonstrated that 48 h of complete fasting prior to Dox administration mitigated the Dox-induced impairment in cardiac function in adult GFP-LC-3 transgenic mice, as determined by left ventricular ejection fraction (LVEF), systolic pressure (LVSP), end diastolic pressure (LVEDP), and +dP/dt. Microscopy revealed attenuation of LV dilatation, myocardial atrophy, and fibrosis [29] .…”
Section: Dox-induced Cardiotoxicitymentioning
confidence: 99%
“…Kawaguchi et al [29] demonstrated that 48 h of complete fasting prior to Dox administration mitigated the Dox-induced impairment in cardiac function in adult GFP-LC-3 transgenic mice, as determined by left ventricular ejection fraction (LVEF), systolic pressure (LVSP), end diastolic pressure (LVEDP), and +dP/dt. Microscopy revealed attenuation of LV dilatation, myocardial atrophy, and fibrosis [29] . In vitro, a caloric restriction mimetic, 2-deoxyglucose (2-DG), was shown to exhibit cardioprotective properties against Dox using neonatal rat cardiomyocytes isolated from 0-2 d old Harlan Sprague-Dawley rat neonates [30] .…”
Section: Dox-induced Cardiotoxicitymentioning
confidence: 99%
See 2 more Smart Citations